2018
DOI: 10.1155/2018/7142325
|View full text |Cite
|
Sign up to set email alerts
|

ROUNDS Studies: Relation of OUtcomes with Nutrition Despite Severity—Round One: Ultrasound Muscle Measurements in Critically Ill Adult Patients

Abstract: Malnutrition (undernutrition) encompasses low intake or uptake, loss of fat mass, and muscle wasting and is associated with worse outcomes. Ultrasound has been introduced in the intensive care unit as a tool to assess muscle mass. The aim of the present study is to explore the relation between initial muscle mass and mortality in adult patients admitted to the intensive care unit. Methods. Rectus femoris and vastus intermedius thicknesses were measured by B-mode ultrasound in adult patients at admission, along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…and Turton et al. referenced the head of bed at a 30° and 45° elevation, respectively, 16,32 while one paper reported a 30°–45° head of bed elevation, 19 and another referenced semi-supine positioning. 33 The term ‘limb extension’ was reported by 21 studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…and Turton et al. referenced the head of bed at a 30° and 45° elevation, respectively, 16,32 while one paper reported a 30°–45° head of bed elevation, 19 and another referenced semi-supine positioning. 33 The term ‘limb extension’ was reported by 21 studies.…”
Section: Resultsmentioning
confidence: 99%
“…5,[12][13][14] Timepoint of assessments. All but seven 8,[14][15][16][17][18][19] authors reported serial US measurements. Of these, only six explicitly reported being conducted after ICU discharge 5,[20][21][22][23][24] (Table 3).…”
Section: Patient Population and Study Designmentioning
confidence: 99%
“…The diagnosis of malnutrition has been challenging due to the absence of a unifying definition; however, it is accepted that malnutrition is associated with a negative accumulated energy balance [2]. This imbalance significantly increases mortality, nosocomial infections, and hospital LOS [3], generating an increase in the costs associated with the treatment [4]. In recent years, it has been reported that the worldwide prevalence of this condition is between 20 and 50% [5].…”
Section: Introductionmentioning
confidence: 99%
“…In our exploratory study, we observed a progressive decline in RFMA, a large proximal extremity muscle, which we utilized as a surrogate for whole-body skeletal muscle mass. 34 We chose to evaluate US RFMA in ICU-bound ESLD patients because of their increased risk for time-dependent critical illness-associated muscle loss, 33 allowing us to demonstrate the feasibility of this modality through serial measurements in a short period of time. The use of US allowed quick, low cost, point-of-care, serial measurement of RFMA, which would be impractical with CT-based techniques.…”
Section: Discussionmentioning
confidence: 99%